Practical and applied hydrogeology - Sen, Zekai (Elsevier, 2015)
Applications in Hydrogeology for Geoscientists presents the most recent scientific developments in the field that are accessible yet rigorous enough for industry professionals and academic researchers alike. A multi-contributed reference that features the knowledge and experience of the field's experts, the book's chapters span the full scope of hydrogeology, introducing new approaches and progress in conceptualization, simulation of groundwater flow and transport, and progressive hydro-geophysical methods. Each chapter includes examples of recent developments in hydrogeology, groundwater,